2021
DOI: 10.3390/ma14237444
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Groove Shape on Molten Metal Flow Behaviour in Gas Metal Arc Welding

Abstract: One of the challenges for development, qualification and optimisation of arc welding processes lies in characterising the complex melt-pool behaviour which exhibits highly non-linear responses to variations of process parameters. The present work presents a computational model to describe the melt-pool behaviour in root-pass gas metal arc welding (GMAW). Three-dimensional numerical simulations have been performed using an enhanced physics-based computational model to unravel the effect of groove shape on compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…User-defined functions (UDFs) programmed in the C programming language were developed to implement the absorptivity model, source and sink terms in the momentum and energy equations as well as the surface tension model in the simulations. As shown in our previous works [3,8,9,52,53], the numerical grid cell spacing should be chosen to have at least 35 cells in the melt pool region along its width. Accordingly, hexahedral cells were used to discretise the computational domain with minimum cell spacing of 50 µm for cases in batch 1 and 2 (CO 2 and Nd:YAG welds, melt-pool widths of about 1500 µm), and 3 µm for cases in batch 3 (continuous wave fibre laser welds, melt-pool widths of about 100 µm), as shown in figure 4.…”
Section: Numerical Implementationmentioning
confidence: 99%
“…User-defined functions (UDFs) programmed in the C programming language were developed to implement the absorptivity model, source and sink terms in the momentum and energy equations as well as the surface tension model in the simulations. As shown in our previous works [3,8,9,52,53], the numerical grid cell spacing should be chosen to have at least 35 cells in the melt pool region along its width. Accordingly, hexahedral cells were used to discretise the computational domain with minimum cell spacing of 50 µm for cases in batch 1 and 2 (CO 2 and Nd:YAG welds, melt-pool widths of about 1500 µm), and 3 µm for cases in batch 3 (continuous wave fibre laser welds, melt-pool widths of about 100 µm), as shown in figure 4.…”
Section: Numerical Implementationmentioning
confidence: 99%
“…Wu et al developed numerical models for the twin-wire [24] and hybrid GMAW process [25] using a comprehensive CFD-based simulation. The mechanisms in uencing the molten pool ow were investigated and simulated in various conditions of driving forces [26], undercut formation [27], transverse magnetic eld [28], arc interactions [29], groove shape [30], double-sided [31], double-shielded [32], and double-pulsed [33] GMAW. The improvement of numerical models is still ongoing, especially in the topics such as wire-arc additive manufacturing (WAAM) [34,35], where new industrial applications are emerging.…”
Section: Introductionmentioning
confidence: 99%
“…The research findings revealed that the presence of the groove promotes smoother flow within the weld pool, leading to inadequate mixing between the filler metal and the base metal. Ebrahimi et al [11]. proposed a computational model that aims to describe the behavior of the melt pool in root-pass gas metal arc welding (GMAW).…”
Section: Introducementioning
confidence: 99%